Evaluasi Skalabilitas Database dalam Mengelola Pertumbuhan Volume Data pada Sistem Informasi Digital: Database Scalability Evaluation in Managing Data Volume Growth in Digital Information Systems - Salinar Winda Br Sagala; Muhammad Irwan Padli Nasution (Pendidikan Al-Gafari, 2026)
The rapid development of digital information systems has led to a significant increase in data volume. This condition demands a database system capable of managing data efficiently without reducing performance. One important aspect in database management is scalability, namely the system's ability to optimally handle data growth and workload. This study aims to evaluate database scalability in managing data volume growth in digital information systems. The research method used is a descriptive qualitative approach with data collection techniques in the form of literature studies from various relevant literature sources. The analysis was conducted by examining the concept of database scalability, the factors that influence it, and the impact of data growth on system performance. The results of the study indicate that data volume growth that is not balanced with good database management can cause a decrease in system performance, such as slow data access and increased server load. Therefore, strategies are needed to improve database scalability, such as query optimization, the use of indexing, caching, and the implementation of vertical and horizontal scalability.